Spin state gradient regulation cobalt monatomic catalyst as well as preparation method and application thereof

The coordination environment and spin state of cobalt single atoms are regulated by sulfur doping gradient, combined with two-stage pyrolysis process and post-treatment method, a high-performance catalyst Co-SxN4-x was prepared, which solved the problem of uncontrollable catalytic mechanism in the existing technology, achieved a coordinated improvement of catalytic activity and stability, and could efficiently remove organic pollutants in water.

CN119793515AActive Publication Date: 2025-04-11HEFEI INSTITUTE OF PHYSICAL SCIENCE CHINESE ACADEMY OF SCIENCES

Patent Information

Application Number
CN202510304317.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-14
Publication Date
2025-04-11
Estimated Expiration
2045-03-14

AI Technical Summary

Technical Problem

The prior art is difficult to effectively regulate the microstructure of the catalytic center, which leads to uncontrollable catalytic mechanisms and difficult to control reaction activity and mechanisms, especially the lack of in-depth analysis on the dominance of spin states on reaction paths.

Method used

The coordination environment and spin state of cobalt single atoms are regulated by sulfur doping gradient, and combined with two-stage pyrolysis process and post-treatment method, the high-performance catalyst Co-SxN4-x was prepared. The method includes loading the cobalt salt on a ZIF-8 metal organic framework, pyrolysis of the temperature is carried out to form a Co-N4 precursor, and then passing in sulfur-containing gas for secondary pyrolysis, so that the sulfur atoms gradually replace nitrogen coordination, and obtaining a spin-state gradient-regulated cobalt single-atom catalyst through acid-base washing treatment.

Benefits of technology

The continuous spin state regulation of cobalt single atoms is achieved, the electronic structure and reaction path are optimized, the catalytic activity and stability are improved, the organic pollutants in water can be efficiently removed, and the efficient catalytic activity is maintained within different pH ranges, avoiding the activity-stability trade-off of traditional catalysts.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119793515A_ABST
    Figure CN119793515A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of water treatment materials, and particularly relates to a spin state gradient regulation cobalt monatomic catalyst and a preparation method and application thereof.The preparation method comprises the steps that cobalt salt is loaded on a metal organic framework material ZIF-8, heating pyrolysis is conducted in an inert atmosphere, and a Co-N4 precursor is formed; after sulfur-containing gas is introduced, secondary heating pyrolysis is carried out, so that nitrogen coordination is gradually replaced by sulfur atoms; and sequentially carrying out acid washing and alkali washing on the pyrolysis product to obtain the spin-state gradient-regulated cobalt monatomic catalyst Co-SxN (4-x), and x is equal to 1-3. The Co and ZIF-8 compound is used as a Co monatomic dispersion template, so that Co atoms are uniformly dispersed in pore channels and nodes of ZIF-8, and metal agglomeration in the high-temperature carbonization process is avoided. And the sulfur doping gradient is utilized to regulate and control the spin state of cobalt monatomic, so that the synergistic improvement of catalytic activity and stability is realized, and the purpose of efficiently degrading and removing organic pollutants in water is achieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of water treatment materials, and in particular, relates to a spin-state gradient-regulated cobalt single-atom catalyst and a preparation method and application thereof. Background Art

[0002] The widespread use of persistent emerging organic pollutants (ECs) such as antibiotics and phenols and their difficult-to-degrade properties have posed a severe challenge to the water environment. The increasing prevalence of ECs has exacerbated the contradiction between water quality deterioration and the escalating demand for clean water resources.

[0003] Heterogeneous advanced oxidation technology based on persulfate can effectively remove ECs from water by producing highly oxidizing active species. However, the correlation between catalytic activity and the complex microstructure of the catalyst is still unclear, and the catalytic mechanism is uncontrollable. Therefore, designing and regulating the microstructure of the catalytic center, deeply understanding the relationship between the catalytic performance of persulfate and the microstructure of the catalyst, and achieving the regulation of reaction activity and mechanism have become the key to the development of this technology.

[0004] Single atom catalysts (SACs) have a unique metal center chemical environment, controllable electronic structure and high metal utilization, and have attracted much attention in the field of heterogeneous catalysis research in recent years. The electron transfer and orbital interaction between the catalyst and the reactants / intermediates show spin-dependent characteristics, and the reaction kinetics / thermodynamics are sensitive to the spin configuration. The spin state type is determined by the number of d-orbital electrons, electron pairing energy, and crystal field splitting energy, which can be regulated by the chemical environment around the metal center. The spin state of the metal center (low spin, medium spin, high spin) has a decisive influence on the catalytic activity. However, existing methods (such as ligand modification) are difficult to achieve continuous gradient regulation of the spin state, and lack an in-depth analysis of the correlation between "chemical environment-spin state-reaction path".

[0005] Although SACs have shown potential in environmental catalysis, existing research has mostly focused on the regulation of coordination environment and coordination number, while ignoring the dominant role of spin state on the reaction path. For example, Chinese patent application publication number CN116637653A discloses an iron single-atom catalyst with controllable sulfur content and coordination mode and its application. Its preparation method includes using nitrogen-allylthiourea and trithiocyanic acid as sulfur-containing organic ligands and sulfur-containing supramolecular precursors, respectively, to chelate with iron ions, and using the supramolecular self-assembly process to control the preparation of iron single-atom catalysts with controllable sulfur content and coordination mode, thereby improving the persulfate activation efficiency and active oxygen species selectivity. However, this invention relies on supramolecular self-assembly and high-temperature cracking processes, with cumbersome steps and difficult to mass-produce. Another example is China's patent application publication number CN117861708A, which discloses a highly coordinated iron single-atom catalyst, preparation method and application thereof for highly selective generation of singlet oxygen by electro-Fenton. The preparation method includes the catalyst using graphite-phase carbon nitride as a carrier, wherein the iron single atom is coordinated with six nitrogen atoms, so that the iron single atom is in a high spin state, and only singlet oxygen is generated during the electro-Fenton process. However, the invention does not establish spin state gradient control, and cannot achieve the coordinated optimization of "coordination-spin-mechanism". Summary of the invention

[0006] The purpose of the present invention is to provide a spin state gradient regulated cobalt single atom catalyst and its preparation method and application in persulfate activated water treatment, which regulates the coordination environment and spin state of cobalt single atoms by sulfur doping gradient, combines a two-stage pyrolysis process with a post-treatment method, and prepares a high-performance catalyst Co-S x N 4-x .

[0007] In order to achieve the above-mentioned purpose of the invention, the technical solution provided by the present invention is as follows: A method for preparing a spin state gradient-regulated cobalt single-atom catalyst comprises the following steps: (1) Loading cobalt salt onto ZIF-8 metal organic framework to form Co@ZIF-8 complex; (2) The Co@ZIF-8 composite is pyrolyzed in an inert atmosphere to form a Co-N4 precursor; (3) After introducing sulfur-containing gas, the temperature is raised for secondary pyrolysis, so that sulfur atoms gradually replace nitrogen coordination; (4) The pyrolysis products were washed with acid and alkali in turn to obtain the spin state gradient-regulated cobalt single atom catalyst Co-S x N 4-x , where x=1~3.

[0008] In a further embodiment, the cobalt salt in step (1) is one of cobalt acetylacetonate, cobalt nitrate, cobalt acetate, cobalt chloride and hydrates thereof.

[0009] In a further embodiment, the inert atmosphere in step (2) is one of N2 and Ar, the heating rate is 5-10°C / min, the temperature is 800-900°C, and the holding time is 1-3h.

[0010] In a further embodiment, the secondary pyrolysis in step (3) is carried out at a heating rate of 5 to 10°C / min, the temperature is raised to 900 to 1100°C, and the temperature is then kept at this temperature for 2 to 4 hours.

[0011] In a further embodiment, the sulfur-containing gas is a mixture of sulfur vapor and a carrier gas (Ar / N2), the volume concentration of sulfur vapor in the sulfur-containing gas is 2-5%; and the flow rate of the sulfur-containing gas is 10-50 sccm.

[0012] The sulfur vapor comes from the sulfur vapor generation and transportation system. High-purity sublimation sulfur powder (purity ≥ 99.9%, particle size < 100μm) is used as the sulfur source, placed in a quartz boat, and then placed in the low-temperature section of an independent temperature zone reactor; the sulfur powder is heated to 200-300°C through a precise temperature control device to sublimate it to generate sulfur vapor. Then an inert gas (Ar or N2) is used as a carrier gas, and its flow rate is adjusted to 10-50sccm by a mass flow meter to carry sulfur vapor into the main reaction zone to undergo a replacement reaction with the Co-N4 precursor. The volume concentration of sulfur vapor in the sulfur-containing gas is accurately controlled by a mass flow meter to be 2-5vol%. The volume concentration of sulfur vapor C s The calculation formula is as follows:

[0013] In the formula, R S is the sulfur sublimation rate (g / min), M S =32.06 g / mol, ρ S is the carrier gas density (g / L), and v is the flow rate.

[0014] In a further embodiment, in step (4), the acid washing is performed by washing the product with one of sulfuric acid, nitric acid and hydrochloric acid at a concentration of 0.5 to 3 M to remove metal particles; The alkali washing is to use one of sodium hydroxide, potassium hydroxide, sodium carbonate and sodium bicarbonate with a concentration of 0.5-2M to wash away unstable sulfur in the product.

[0015] The second invention objective of the present invention is to provide a spin state gradient regulated cobalt single atom catalyst Co-S x N 4-x , which is prepared by the above-mentioned preparation method.

[0016] In a further embodiment, the spin state gradient is used to regulate the cobalt single atom catalyst Co-S x N 4-x The central effective magnetic moment of a single cobalt atom is 2.259 to 3.147 μB , the corresponding spin state is continuously regulated from medium-spin Co-S1N3 to high-spin Co-S3N1; The sulfur doping ratio is controlled by increasing the pyrolysis temperature and the gradient of sulfur vapor concentration, and the S / N atomic ratio is satisfied to be 1:3 to 3:1.

[0017] In a further embodiment, the spin state gradient is used to regulate the cobalt single atom catalyst Co-S x N 4-x The specific surface area is ≥800m² / g, and the loading mass of cobalt single atoms is 0.5-1.5%.

[0018] The third invention object of the present invention is to provide the above-mentioned catalyst Co-S x N 4-x Its application is to catalyze the degradation of organic pollutants in wastewater.

[0019] In a further solution, the catalyst Co-S x N 4-x It is added into wastewater for ultrasonic dispersion, and then persulfate is added for catalytic degradation reaction to remove organic pollutants in the wastewater.

[0020] In a further embodiment, based on the volume of wastewater, the catalyst Co-S x N 4-x The amount of addition is 50-500 mg / L, and the amount of peroxide added is 20-300 mg / L; And / or, the reaction liquid pH of the catalytic degradation reaction is 3-11, the reaction temperature is 20-50° C., and the reaction time is 10-60 min.

[0021] In a further embodiment, the persulfate is any one of potassium peroxymonosulfate, sodium peroxymonosulfate, potassium peroxodisulfate, and sodium peroxodisulfate; The organic pollutants include tetracycline (TC), sulfadiazine (SDZ), sulfamethoxazole (SMX), sulfisoxazole (SIZ), bisphenol A (BPA) or phenol (PhOH).

[0022] The present invention has the following beneficial effects: (1) The present invention utilizes sulfur doping gradient to control the spin state of cobalt single atoms and optimize their electronic structure and reaction path. Specifically: Continuous control of spin states: sulfur atoms gradient replace nitrogen coordination (Co-S x N 4-x , x = 1 to 3), using the S gradient of weak ligand field strength to replace the N of strong ligand field strength, reducing the crystal field splitting energy, and making the cobalt center spin state continuously transform to high spin Co-S3N1 compared with the medium spin Co-S1N3. And due to sulfur doping, t2g The orbital electrons occupy less space, e g The increased orbital electron occupancy can enhance the hybridization efficiency of the Co 3d orbital and the O 2p orbital in persulfate.

[0023] Dynamic evolution of the d-band center: The low electronegativity of sulfur (χ=2.58) increases the electron density of cobalt, causing the d-band center (Ed) to move toward the Fermi level. The upward shift of the d-band center optimizes the adsorption-activation balance between Co and PMS: moderate Ed (such as Co-S1N3 in the medium spin state) partially fills the antibonding orbital (σ * or π * ), which not only enhances the adsorption of persulfate, but also avoids the increase of the intermediate desorption energy barrier caused by excessive adsorption.

[0024] (2) The present invention utilizes sulfur doping gradient to control the spin state of cobalt single atoms to achieve directional enhancement of non-radical electron transfer pathway (ETP). Specifically: Orbital hybridization and electron transfer: Sulfur doping enhances Co 3d-O 2p orbital hybridization, promotes the adsorption of persulfate, forms a stable persulfate surface complex intermediate, and promotes the transfer of electrons from pollutants to persulfate surface complexes. Appropriate sulfur doping improves the ability of Co active centers to accept and contribute electrons, improves the interfacial charge transfer kinetics, and is conducive to the strong interaction between persulfate surface complexes and organic pollutants.

[0025] Path switching mechanism: Sulfur doping reduces the valence state of Co, weakens the oxidation ability of Co, inhibits the generation of traditional free radicals or high-valent cobalt oxide species (Co (IV) = O), and instead directly oxidizes pollutants through ETP, thereby improving the degradation ability of organic pollutants in water.

[0026] (3) The present invention utilizes sulfur doping gradient to regulate the spin state of cobalt single atoms, thereby achieving a synergistic improvement in catalytic activity and stability, thereby achieving the purpose of degrading and removing organic pollutants in water. Specifically: Volcano-type activity trend: The coordinated regulation of the spin state of single cobalt atoms and the d-band center makes the catalytic activity present a volcano-type curve. The reaction activity of (Co-S1N3) with an intermediate spin state reaches a peak, balancing the adsorption energy and electron transfer efficiency, becoming the peak point of performance, which is better than traditional Co-N4 and most cobalt-based catalysts reported in the literature (such as Co3O4, etc.).

[0027] Anti-interference and universality: The non-radical ETP mechanism is affected by humic acid (HA) and most ions (Cl ⁻ 、HCO3 ⁻ 、SO4 ²⁻ In addition, it maintains high catalytic activity in the pH range of 3 to 11, breaking through the acid dependence of the traditional Fenton system.

[0028] Ultra-low metal leaching and cycle stability: The acid / alkali double washing process removes unstable metals and sulfur species, with low cobalt leaching, strong recyclability and stable structure.

[0029] (4) The present invention utilizes sulfur doping gradient to control the spin state of cobalt single atoms, achieving scientific value and technological innovation, specifically: Quantitative spin state-activity model: Establish a three-dimensional correlation model of sulfur doping gradient, spin state and reaction path, providing a theoretical framework for the rational design of single-atom catalysts.

[0030] Dynamic mechanism analysis: reveal the dynamic process of Co 3d orbital reconstruction induced by sulfur doping, clarify the synergistic mechanism of "adsorption-electron transfer-desorption", and promote the in-depth research on the mechanism of advanced oxidation technology.

[0031] (5) The present invention uses the Co@ZIF-8 complex as a template for the dispersion of Co single atoms, so that the Co atoms are evenly dispersed in the pores and nodes of ZIF-8, avoiding metal agglomeration during high-temperature carbonization. The imidazole ligands of ZIF-8 contain nitrogen atoms, which can form a stable Co-N coordination bond with Co²⁺. This coordination environment is retained during the carbonization process to form a Co-N x Active sites directly affect the electronic structure of the catalyst. In addition, during the sulfur doping process, the microporous structure of ZIF-8 adsorbs sulfur molecules, ensuring that sulfur atoms are evenly distributed, and sulfur atoms partially replace nitrogen in the Co-N coordination to form Co-S x N 4-x Mixed coordination structure to further optimize the electronic structure.

[0032] (6) The present invention realizes the gradient doping and coordination structure reconstruction of sulfur atoms and the continuous regulation of spin states through secondary temperature pyrolysis. High temperature promotes the graphitization of the carbon matrix and enhances the stability of the carrier. At the same time, the sulfur atoms form a strong bond (Co-S bond) with cobalt to prevent sintering or loss of active sites.

[0033] (7) The present invention achieves gas phase doping by introducing sulfur vapor to precisely control the coordination environment of cobalt, thereby avoiding uneven doping caused by solid sulfur source doping.

[0034] (8) Co-S prepared by the present invention x N 4-x Acid washing is required to wash away metal particles, and then alkaline washing is required to wash away unstable sulfur, thereby improving the purity, active site uniformity and stability of the final product.

[0035] Therefore, the present invention regulates the spin state and electronic structure of single cobalt atoms through sulfur doping gradient, breaks through the activity-stability trade-off of traditional catalysts, realizes efficient and green water treatment via non-radical pathways, and provides an optimal solution for the atomic-level design of environmental functional materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 The catalysts prepared in Example 1 are Co-N4 and Co-S4 prepared in Examples 1 to 3. x N 4-x TEM images, wherein a is the TEM image of Co-N4 in Comparative Example 1, b is the TEM image of Co-S1N3 in Example 1, c is the TEM image of Co-S2N2 in Example 2, and d is the TEM image of Co-S3N1 in Example 3; Figure 2 The catalysts prepared in Example 1 are Co-N4 and Co-S4 prepared in Examples 1 to 3. x N 4-x X-ray absorption fine structure (XAFS) test results, where a is Co-N4, catalyst Co-S x N 4-x and the Co K-edge X-ray absorption near-edge structure (XANES) spectra of the comparative samples, b is the Fourier transform extended X-ray absorption fine structure (FT-EXAFS) spectrum; Figure 3 The catalysts prepared in Example 1 are Co-N4 and Co-S4 prepared in Examples 1 to 3. x N 4-x BET chart; Figure 4 The catalysts prepared in Example 1 are Co-N4 and Co-S4 prepared in Examples 1 to 3. x N 4-x Magnetic susceptibility curve test diagram; Figure 5 The catalysts prepared in Example 1 are Co-N4 and Co-S4 prepared in Examples 1 to 3. x N 4-x The effect of activated potassium peroxymonosulfate on the degradation of sulfadiazine; Figure 6 The catalysts prepared in Example 1 are Co-N4 and Co-S4 prepared in Examples 1 to 3. x N 4-x Active species contribution diagram of the degradation of sulfadiazine by activated potassium peroxymonosulfate. DETAILED DESCRIPTION

[0037] The present invention is further described below in conjunction with specific embodiments, but the essence of the present invention is not limited to the following embodiments. The methods are conventional methods unless otherwise specified, and the materials can be obtained from public commercial channels unless otherwise specified. Those skilled in the art should know that any simple transformation or substitution based on the essence of the present invention belongs to the protection scope claimed by the present invention.

[0038] The metal organic framework material ZIF-8 in the present application is 2-methylimidazole zinc MOF, which is obtained by mixing zinc salt and organic ligand in a suitable solvent and heating the mixture. Commonly used organic solvents include N,N-dimethylformamide (DMF), ethylene glycol and methanol.

[0039] The preparation method of the metal organic framework material ZIF-8 is known. The specific preparation method of the metal organic framework material ZIF-8 in each embodiment of the present application is as follows: 2.14 g of zinc nitrate hexahydrate was dissolved in 50 mL of methanol solution, and 2.32 g of dimethylimidazole was dissolved in 50 mL of methanol solution. The two solutions were mixed, stirred at room temperature for 12 h, centrifuged and washed, and then vacuum dried at 60° C. for 10 h to obtain the metal organic framework material ZIF-8.

[0040] Embodiment 1: (1) 1.2 g ZIF-8 and 0.05 g cobalt acetylacetonate were added to 50 mL methanol solution, stirred at room temperature for 12 h, and then centrifuged and dried to obtain the Co@ZIF-8 complex; (2) The Co@ZIF-8 composite was heated to 800 °C in Ar at a heating rate of 5 °C / min for pyrolysis, and then kept at this temperature for 3 h to form a Co-N4 precursor; (3) Then, sulfur-containing vapor (the volume concentration of sulfur vapor in the sulfur-containing gas is 2% and the flow rate is 20 sccm) is introduced, and the temperature is raised to 900°C at a heating rate of 5°C / min for secondary pyrolysis, and then kept at this temperature for 3 hours, so that sulfur atoms gradually replace nitrogen coordination; (4) The pyrolysis product was acid-washed in a 1M HNO3 solution for 12 h, centrifugally washed, and then dried in a vacuum at 60°C for 10 h; then alkaline-washed in a 1M NaOH solution for 2 h, centrifugally washed, and then dried in a vacuum at 60°C for 10 h. The resulting catalyst was designated Co-S1N3.

[0041] Comparative Example 1: (1) 1.2 g ZIF-8 and 0.05 g cobalt acetylacetonate were added to 50 mL methanol solution, stirred at room temperature for 12 h, and then centrifuged and dried to obtain the Co@ZIF-8 complex; (2) The Co@ZIF-8 composite was heated to 800°C at 5°C / min in an Ar atmosphere, kept at this temperature for 3 h, and naturally cooled to form a Co-N4 precursor; (3) The catalyst was acid-washed in 1 M HNO3 solution for 12 h, then centrifuged and dried in vacuum at 60 °C for 10 h. The obtained catalyst was denoted as Co-N4.

[0042] Embodiment 2: The same as Example 1, except that the temperature of the secondary pyrolysis in step (3) is 1000° C. The obtained catalyst is denoted as Co-S2N2.

[0043] Embodiment 3: The same as Example 1, except that the temperature of the secondary pyrolysis in step (3) is 1100° C. The obtained catalyst is denoted as Co-S3N1.

[0044] Test example 1: The catalysts Co-N4, Co-S1N3, Co-S2N2, and Co-S3N1 prepared from the catalysts in Comparative Example 1 and Examples 1 to 3 were subjected to relevant tests, and the test results are as follows: (1) Figure 1 a is the TEM image of Co-N4, b is the TEM image of Co-S1N3, c is the TEM image of Co-S2N2, and d is the TEM image of Co-S3N1. x N 4-x The catalyst has a similar polyhedral morphology and no nanoclusters or particles are observed. The doping of S and the increase in temperature cause the Co-N part to break at high temperature, so the catalyst becomes rougher and more porous. This structural change significantly increases the specific surface area, active site exposure rate and mass transfer efficiency of the catalyst.

[0045] (2) Figure 2 Catalysts Co-N4, Co-S x N 4-x XAFS test results. Figure a shows the catalyst Co-N4, Co-S x N 4-x Co K-edge XANES spectra of the samples and the comparison samples (in the figure, "CoFoil" is cobalt foil, "CoO" is cobaltous oxide, "Co3O4" is cobalt tetraoxide, the vertical axis "Normalizedxμ(E)" represents the normalized X-ray absorption intensity, and "Energy" represents the energy of the X-ray (unit: electron volt)). The results show that with the doping of S, Co-S x N 4-x The valence gradually decreases.

[0046] Figure b is the FT-EXAFS spectrum, where the Co-N scattering path of the Co-N4 sample is observed. After S doping, the Co-S scattering path is observed. With the doping of S, the intensity of the Co-N path decreases, while the intensity of the Co-S increases. x N 4-x The single-atom structure of Co was confirmed because no Co-Co scattering path was observed. After the coordination environment was fitted and quantified, the catalyst structures in Comparative Example 1 and Examples 1 to 3 were determined to be Co-N4, Co-S1N3, Co-S2N2, and Co-S3N1, respectively. This further confirmed the gradient regulation of the coordination environment of Co single atoms.

[0047] (3) Figure 3 The catalysts Co-N4, Co-S prepared in Comparative Example 1 and Examples 1 to 3 are x N 4-x The results show that the BET surface areas of Co-N4, Co-S1N3, Co-S2N2 and Co-S3N1 are 755.2, 899.5, 930.2, 950.9 m 2 / g. With the increase of temperature, the surface area increases, which is mainly due to the etching effect at high temperature, which increases the total pore volume.

[0048] (4) Inductively coupled plasma optical emission spectroscopy (ICP-OES) determined that the loading mass of Co in Co-N4, Co-S1N3, Co-S2N2, and Co-S3N1 were 0.86%, 0.88%, 0.90%, and 0.84%, respectively.

[0049] (5) Figure 4 For comparative example 1, Co-N4 and Co-S prepared in Examples 1 to 3 x N 4-x The magnetic susceptibility curve of the catalyst (measured by superconducting quantum interference instrument under H=1 KOe). The results show that Co-S x N 4-x The central effective magnetic moment (μ) of a single cobalt atom in the catalyst eff ) are 1.630μ B (Co-N4), 2.259μ B (Co-S1N3), 3.045μ B (Co-S2N2), 3.147μ B(Co-S3N1), the calculated unpaired electron numbers are 0.912, 1.470, 2.205, and 2.302, respectively. Therefore, the spin state of Co follows the order of Co-N4<Co-S1N3<Co-S2N2<Co-S3N1. With the doping of S, the ligand field strength weakens, the crystal field splitting energy decreases, and the spin state increases. The feasibility of the sulfur doping gradient method to control the coordination environment and spin state of cobalt single atoms is confirmed.

[0050] Test example 2: Experiment on degradation of sulfadiazine in wastewater by activated peroxymonosulfate: 8 mg of each of the catalysts Co-N4, Co-S1N3, Co-S2N2, and Co-S3N1 prepared in Comparative Example 1 and Examples 1 to 3 were weighed and added to a water sample containing 100 mL of sulfadiazine (denoted as C0) at a concentration of 20 mg / L, and then 30 mg of potassium peroxymonosulfate was added to each sample, the pH value was adjusted to 7, and the reaction was carried out at 25°C. After being fully shaken at 180 rpm in a shaker, samples were taken at certain time intervals (such as taking water samples at 0, 2, 5, 10, 20, and 30 minutes, respectively), and the sulfadiazine content (denoted as C) in the water sample was detected by high performance liquid chromatography after filtration, as shown in detail. Figure 5 As shown in the figure, after 30 minutes of reaction, the removal rates of sulfadiazine by Co-N4, Co-S1N3, Co-S2N2, and Co-S3N1 activated PMS were 65.3%, 100%, 94.6%, and 91.2%, respectively. The reaction rate value (kobs) followed the Co-S1N3 (0.178 min -1 )>Co-S2N2(0.090 min -1 )>Co-S3N1(0.074 min -1 )>Co-N4(0.029 min -1 ) in the order of .

[0051] Test example 3: Benzoic acid, nitrobenzene, p-chlorobenzoic acid, furfuryl alcohol and methyl phenyl sulfoxide were used as the quantitative detection of hydroxyl radicals (·OH) and sulfate radicals (SO4 ·- ), superoxide radicals (O2 ·- )、Singlet oxygen( 1 The contribution of different active species in Example 2 was quantitatively detected by competitive kinetics. The results are shown in Figure 6As shown in the figure, Co(IV)=O contributes 69.6% in the Co-N4 / PMS system, dominating the degradation of sulfadiazine. However, with the gradual substitution of S for N, the reaction pathway changes, and the contributions of electron transfer (ETP) in the Co-S1N3 / PMS, Co-S2N2 / PMS, and Co-S3N1 / PMS systems are 84.9%, 50.2%, and 41.1%, respectively.

[0052] Embodiment 4: (1) Add 1.0 g ZIF-8 and 0.08 g anhydrous cobalt chloride into 100 mL methanol solution, stir at room temperature for 12 h, and then centrifuge and dry to obtain the Co@ZIF-8 complex; (2) The Co@ZIF-8 composite was heated to 850°C in Ar at a heating rate of 7°C / min for pyrolysis, and then kept at this temperature for 2 h to form a Co-N4 precursor; (3) Then, sulfur-containing vapor (the volume concentration of sulfur vapor in the sulfur-containing gas is 3% and the flow rate is 30 sccm) is introduced, and the temperature is raised to 900°C at a heating rate of 7°C / min for secondary pyrolysis, and the temperature is kept for 4 hours, so that sulfur atoms gradually replace nitrogen coordination; (4) The pyrolysis product was acid-washed in a 0.5 M H2SO4 solution for 24 h, centrifugally washed and then dried in a vacuum at 60°C for 10 h; then alkaline-washed in a 1 M KOH solution for 2.5 h, centrifugally washed and then dried in a vacuum at 60°C for 10 h. The resulting catalyst was designated as Co-S1N3.

[0053] Comparative Example 2: The same as comparative example 1, except that 1.0 g ZIF-8 and 0.08 g anhydrous cobalt chloride were added to 100 mL methanol solution, stirred at room temperature for 12 h, and then centrifuged and dried to obtain a Co@ZIF-8 complex.

[0054] The final catalyst was recorded as Co-N4'.

[0055] Comparative Example 3: The same as Example 4, except that the flow rate of sulfur vapor is 0 sccm, and the obtained catalyst is denoted as Co-NC-900.

[0056] Comparative Example 4: The same as Example 4, except that the temperature of the secondary pyrolysis is 800° C., and the obtained catalyst is denoted as Co-SNC-800.

[0057] Comparative Example 5: The same as Example 4, except that the temperature of the secondary pyrolysis is 1500° C., and the obtained catalyst is denoted as Co-SNC-1500.

[0058] Comparative Example 6: (1) The preparation of Co@ZIF-8 composite was the same as in Example 4; (2) introducing sulfur-containing vapor (the volume concentration of sulfur vapor in the sulfur-containing gas is 5% and the flow rate is 30 sccm), heating the Co@ZIF-8 composite to 900°C in Ar at a heating rate of 10°C / min, and then keeping the temperature for 2h to form a Co-SNC' precursor; (3) The catalyst was acid-washed in 0.5 M H2SO4 solution for 24 h, centrifugally washed and then dried in vacuum at 60 °C for 10 h; then alkaline-washed in 1 M KOH solution for 2.5 h, centrifugally washed and then dried in vacuum at 60 °C for 10 h. The obtained catalyst was denoted as Co-SNC'.

[0059] Comparative Example 7: (1) 1.0 g of glucose, 0.5 g of melamine and 0.08 g of anhydrous cobalt chloride were added to 100 mL of methanol solution, stirred at room temperature for 12 h and then centrifuged and dried to obtain a Co-NC composite; (2) introducing sulfur-containing vapor (the volume concentration of sulfur vapor in the sulfur-containing gas is 5% and the flow rate is 30 sccm), heating the Co-NC composite to 900 °C in Ar at a heating rate of 10 °C / min for pyrolysis, and then keeping the temperature for 2 h to form Co-SNC; (3) The catalyst was acid-washed in 0.5 M H2SO4 solution for 24 h, centrifuged and dried in vacuum at 60°C for 10 h; then alkaline-washed in 1 M KOH solution for 2.5 h, centrifuged and dried in vacuum at 60°C for 10 h. The obtained catalyst was recorded as "Co-SNC".

[0060] Test example 4: As in Test Example 2, 5 mg of the catalysts prepared in Experimental Example 4 and Comparative Examples 2-7 were added to 100 mL of bisphenol A (content 15 mg / L) water sample, and then 2 mg of sodium peroxymonosulfate was added to adjust the pH value to 3. The mixture was shaken at 200 rpm in a shaker at 50°C. After 60 minutes, samples were taken to detect the concentration of bisphenol A in the water samples. The results are shown in Table 1.

[0061] Test example 5: The same as in Detection Example 3, the contribution rate of the active species that plays a key role in the reaction process in Detection Example 4 was quantitatively detected. The results are shown in Table 1.

[0062] Table 1:

[0063] Compared with Co-S1N3 prepared in Example 4, the catalyst Co-N4' prepared in Comparative Example 2 has no sulfur doping regulation, the spin state of the Co atom is low, and the ability to bind with persulfate is poor, which makes it easier to generate Co(IV)=O during the catalytic process and the catalytic effect is poor.

[0064] The Co-NC-900 prepared in Comparative Example 3 is sulfur-free, has a reduced nitrogen content and an increased carbon content compared to Comparative Example 2, and a lower steady-state concentration of Co(IV)=O.

[0065] In the Co-SNC-800 prepared in Comparative Example 4, the temperature of the secondary pyrolysis was 800°C, resulting in limited substitution of sulfur for nitrogen, and the spin state of Co atoms was slightly improved compared with Co-N4. However, the catalytic effect was reduced compared with that of Example 4.

[0066] In the Co-SNC-1500 prepared in Comparative Example 5, the temperature of the secondary pyrolysis was 1500°C. The high temperature resulted in the aggregation of cobalt clusters and the formation of cobalt sulfide, which was removed during the acid washing process. The Co content in the catalyst was reduced and nanoparticles were present. SO4 ·- Dominates the degradation of bisphenol A.

[0067] In Comparative Example 6, Co-SNC' was prepared by a single direct pyrolysis method. ZIF-8 carbonization and sulfur doping were carried out simultaneously. The sulfur atoms may directly compete with the incompletely formed Co-N bonds, resulting in uneven sulfur doping and removal in the alkaline washing step. Sulfur and nitrogen atoms randomly occupy coordination sites at high temperatures, making it difficult to accurately control the sulfur doping gradient; and the spin states of Co atoms are randomly distributed, making it difficult to optimize dp hybridization.

[0068] Comparative Example 7: Co-SNC prepared by using Co-NC composite (without ZIF-8 template), in which Co atoms are partially agglomerated and nitrogen is unevenly distributed, the specific surface area is reduced, and SO4 ·- Dominates the degradation of bisphenol A.

[0069] Embodiment 5: (1) 1.0 g ZIF-8 and 0.10 g cobalt acetate were added to 100 mL methanol solution, stirred at room temperature for 12 h, and then centrifuged and dried to obtain the Co@ZIF-8 complex; (2) The Co@ZIF-8 composite was first placed in Ar, heated to 800 °C at a heating rate of 5 °C / min for pyrolysis, and then kept at this temperature for 2 h to form a Co-N4 precursor; (3) introducing sulfur vapor (the volume concentration of sulfur vapor in the sulfur-containing gas is 5% and the flow rate is 25 sccm), then heating up to 900°C at a heating rate of 5°C / min and keeping the temperature for 3 hours for secondary heating pyrolysis, so that sulfur atoms gradually replace nitrogen coordination; (4) The pyrolysis product was acid-washed in a 0.5 M H2SO4 solution for 12 h, centrifugally washed and then dried in a vacuum at 60°C for 10 h; then alkaline-washed in a 1 M KOH solution for 2.5 h, centrifugally washed and then dried in a vacuum at 60°C for 10 h. The resulting catalyst was designated as Co-S1N3.

[0070] Embodiment 6: (1) 1.0 g ZIF-8 and 0.10 g cobalt acetate were added to 100 mL methanol solution, stirred at room temperature for 12 h, and then centrifuged and dried to obtain the Co@ZIF-8 complex; (2) The Co@ZIF-8 complex was first placed in N2 and heated to 900°C at a heating rate of 10°C / min for pyrolysis, and then kept at this temperature for 1 h to form a Co-N4 precursor; (3) introducing sulfur-containing vapor (the volume concentration of sulfur vapor in the sulfur-containing gas is 5% and the flow rate is 50 sccm), heating the temperature to 1000°C at a heating rate of 10°C / min and keeping the temperature for 2 hours for secondary heating pyrolysis, so that sulfur atoms gradually replace nitrogen coordination; (4) The pyrolysis product was acid-washed in a 0.5 M H2SO4 solution for 12 h, centrifugally washed and then dried in a vacuum at 60°C for 10 h; then alkaline-washed in a 1 M KOH solution for 4 h, centrifugally washed and then dried in a vacuum at 60°C for 10 h. The resulting catalyst was recorded as Co-S2N2.

[0071] Comparative Example 8: Weigh 100 mg of cobalt nitrate hexahydrate, 200 mg of gallic acid, and 4 g of thiocyanate powder, mix them, add them to 20 mL of ethanol, stir, and dry them at 80°C; The mixture was placed in a tube furnace, heated from room temperature to 800°C at a rate of 5°C / min, and kept at this temperature for 2 h, with nitrogen protection during calcination; After calcination, the mixture was naturally cooled to room temperature. The obtained black powder was soaked in 0.5 M dilute sulfuric acid for 12 h, then washed with water until neutral, and dried in vacuum. The obtained catalyst was recorded as Co-SNC.

[0072] Test Example 6: Same as in Test Example 2, 50 mg of each of the catalysts Co-S1N3, Co-S2N2, and Co-SNC prepared in the above Experimental Examples 5 and 6 and Comparative Example 8 were added to 100 mL of phenol (20 mg / L) water sample, and then 30 mg of potassium peroxydisulfate was added, the pH was adjusted to 11, and the mixture was fully shaken at 200 rpm in a shaker at 20°C. After 30 minutes, samples were taken to detect the concentration of phenol in the water samples, and the degradation removal rates were 100.0%, 91.2%, and 78.8%, respectively.

[0073] Test example 7: The same as detection example 3, quantitatively detect the contribution rate of active species that play a key role in the reaction process in example 6. The contribution rates of ETP in Co-S1N3 / PMS, Co-S2N2 / PMS, and Co-SN / PMS systems are 91.8%, 80.4%, and 66.4%, respectively.

[0074] The present application adopts the method of introducing sulfur vapor for sulfur doping, while in Comparative Example 8, sulfur powder is added, wherein the sulfur powder is easy to cause local over-doping, making the distribution of active sites of the prepared catalyst uncontrollable, resulting in too high spin state of the Co center, too strong adsorption with persulfate, increased energy barrier for desorption of intermediates, too many unpaired electrons are easy to transfer to the peroxide bond of persulfate to break it, and the catalytic performance is limited.

[0075] From the above, it can be concluded that sulfur doping in this application regulates the continuous evolution of Co spin state, and sulfur doping promotes the increase of spin state by reducing the crystal field splitting energy. In addition, the low electronegativity of sulfur increases the electron density of cobalt, and the d-band center moves toward the Fermi level, optimizing the PMS adsorption and activation balance. And the catalytic activity (kobs) shows a volcano-shaped curve with the sulfur doping amount (x). The Co 3d-O 2p orbital hybridization efficiency of the medium spin state Co-S1N3 is the highest, which promotes ETP and further improves the removal of pollutants, and its removal rate reaches more than 90%. The present invention realizes the directional optimization of "chemical environment-electronic structure-reaction path" through the three-dimensional design of sulfur doping gradient, coordination number and spin state.

[0076] Finally, it should be noted that the above embodiments are only preferred implementations of the present invention and are only used to explain the present invention, not to limit the present invention. For those skilled in the art, they can still modify the technical solutions recorded in the above embodiments, or replace some of the technical features therein with equivalents. Any changes, replacements and modifications made within the spirit and principles of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a spin-state gradient-regulated cobalt single-atom catalyst, characterized in that: The following steps are involved: (1) Loading cobalt salt on the metal organic framework material ZIF-8 to form a Co@ZIF-8 complex; (2) The Co@ZIF-8 composite is pyrolyzed in an inert atmosphere to form a Co-N4 precursor; (3) After introducing sulfur-containing gas, the temperature is raised for secondary pyrolysis, so that sulfur atoms gradually replace nitrogen coordination; (4) The pyrolysis products were washed with acid and alkali in turn to obtain the spin state gradient-regulated cobalt single atom catalyst Co-S x N 4-x , where x=1~3.

2. The preparation method according to claim 1, characterized in that: The cobalt salt in step (1) is one of cobalt acetylacetonate, cobalt nitrate, cobalt acetate, cobalt chloride and hydrates thereof.

3. The preparation method according to claim 1, characterized in that: In step (2), the inert atmosphere is N2 or Ar, and the heating pyrolysis is carried out at a heating rate of 5 to 10°C / min, the temperature is raised to 800 to 900°C, and the heat preservation time is 1 to 3 hours.

4. The preparation method according to claim 1, characterized in that: In step (3), the secondary heating pyrolysis is carried out at a heating rate of 5 to 10°C / min, the temperature is raised to 900 to 1100°C, and the temperature is then kept at this temperature for 2 to 4 hours.

5. The preparation method according to claim 1, characterized in that: The sulfur-containing gas is a mixture of sulfur vapor and carrier gas (Ar / N2), the volume concentration of sulfur vapor in the sulfur-containing gas is 2-5%; the flow rate of the sulfur-containing gas is 10-50 sccm.

6. The preparation method according to claim 1, characterized in that: In step (4), the acid washing is performed by using one of sulfuric acid, nitric acid and hydrochloric acid with a concentration of 0.5 to 3 M to wash away metal particles from the product; The alkali washing is to use one of sodium hydroxide, potassium hydroxide, sodium carbonate and sodium bicarbonate with a concentration of 0.5-2M to wash away unstable sulfur from the product.

7. A spin-state gradient-regulated cobalt single-atom catalyst Co-S x N 4-x , characterized in that: The method is prepared according to any one of claims 1 to 6.

8. A spin state gradient regulated cobalt single atom catalyst Co-S according to claim 7 x N 4-x , characterized in that: The catalyst Co-S x N 4-x The central effective magnetic moment of a single cobalt atom is 2.259 to 3.147 μ B , the corresponding spin state is continuously regulated from medium-spin Co-S1N3 to high-spin Co-S3N1; The sulfur doping ratio is controlled by increasing the pyrolysis temperature and the gradient of sulfur vapor concentration, and the S / N atomic ratio is satisfied to be 1:3 to 3:

1.

9. A spin state gradient regulated cobalt single atom catalyst Co-S according to claim 7 x N 4-x , characterized in that: The catalyst Co-S x N 4-x The specific surface area is ≥800m² / g, and the loading mass of cobalt single atoms is 0.5-1.5%.

10. A spin state gradient regulated cobalt single atom catalyst Co-S as claimed in any one of claims 7 to 9 x N 4-x The application is characterized by: It is used for catalytic degradation of organic pollutants in wastewater.

11. The use according to claim 10, characterized in that: First, the catalyst Co-S x N 4-x It is added into wastewater for ultrasonic dispersion, and then persulfate is added for catalytic degradation reaction to remove organic pollutants in the wastewater.

12. The use according to claim 11, characterized in that: Based on the volume of wastewater, the catalyst Co-S x N 4-x The amount of addition is 50-500 mg / L, and the amount of peroxide added is 20-300 mg / L; And / or, the pH value of the reaction liquid of the catalytic degradation reaction is 3-11, the reaction temperature is 20-50° C., and the reaction time is 10-60 min; And / or, the persulfate is any one of potassium peroxymonosulfate, sodium peroxymonosulfate, potassium peroxodisulfate, and sodium peroxodisulfate; And / or, the organic pollutants include tetracycline, sulfadiazine, sulfamethoxazole, sulfisoxazole, bisphenol A or phenol.

Citation Information

Patent Citations

  • Catalyst for efficiently catalyzing and degrading sulfonamide antibiotics, and preparation method and application thereof

    CN112958094A

  • Preparation method and application of asymmetric coordination monatomic catalyst

    CN114086212A

  • Method for degrading sulfamethoxazole by wood sponge cooperating with thermal activation persulfate

    CN114146722A

  • Porphyrin metal organic framework derived metal single atom and atom cluster co-loaded porous carbon material as well as preparation method and application of porphyrin metal organic framework derived metal single atom and atom cluster co-loaded porous carbon material

    CN117976919A

Cited By

  • Iron-based metal-organic complex catalyst, preparation method and method for removing ofloxacin in water body

    CN120394094A

  • Composite catalyst cooperatively regulated by near-end coordination and far-end cluster as well as preparation method and application of composite catalyst

    CN122141770A

  • A composite catalyst synergistically regulated by proximal coordination and distal cluster, a preparation method and application thereof

    CN122141770B